HUMAN IMMUNITY TO THE MENINGOCOCCUS : II. DEVELOPMENT OF NATURAL IMMUNITY - Goldschneider, Irving (The Rockefeller University Press, 1969)
Results of the present study suggest that natural immunity to meningococcal disease is initiated, reinforced, and broadened by intermittent carriage of different strains of meningococci throughout life. In young adults, carriage of meningococci in the nasopharynx is an efficient process of immune sensitization. 92% of carriers of serogroup B, C, or Bo meningococci were found to develop increased titers of serum bactericidal activity to their own meningococcal isolate, and 87% developed bactericidal activity to heterologous strains of pathogenic meningococci. The rise in bactericidal titer occurred within 2 wk of onset of the carrier state, and was accompanied by an increase in titer of specific IgG, IgM, and IgA antibodies to meningococci. In early childhood, when few children have antibodies to pathogenic meningococci, active immunization seems to occur as a result of carriage of atypical, nonpathogenic strains. Immunity to systemic meningococcal infection among infants in the neonatal period is associated with the passive transfer of IgG antibodies from mother to fetus. The antigenic determinants which initiate the immune response to meningococci include the group-specific C polysaccharide, cross-reactive antigens, and type-specific antigens.